Digital twin assisted surgery, concept, opportunities, and challenges - Lisa Asciak; Justicia Kyeremeh; Xichun Luo; Asimina Kazakidi; Patricia Connolly; Frederic Picard; Kevin O’Neill; Sotirios A. Tsaftaris; Grant D. Stewart; Wenmiao Shu (npj Digital Medicine)
Abstract Computer-assisted surgery is becoming essential in modern medicine to accurately plan, guide, and perform surgeries. Similarly, Digital Twin technology is expected to be instrumental in the future of surgery, owing to its capacity to virtually replicate patient-specific interventions whilst providing real-time updates to clinicians. This perspective introduces the term Digital Twin-Assisted Surgery and discusses its potential to improve surgical precision and outcome, along with key challenges for successful clinical translation.